Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species - Danilov, Yuriy N. (Zootaxa, 2017)
Nine species of Podalonia are treated. Lectotypes are designated for Ammophila andrei F. Morawitz, 1889 and Ammophila kozlovii Kohl, 1906. Four new species are described and illustrated: P. asiatica (Russia, China, and Mongolia), P. gussakovskii (Tajikistan), P. kazenasi (Kazakhstan), and P. nazarovae (Tajikistan). The hitherto unknown females of P. albohirsuta Tsuneki, 1971 and P. hirsutaffinis (Tsuneki, 1971) are described. Additional information is provided for the males of P. andrei (F. Morawitz, 1889) and P. kozlovii (Kohl, 1906). Podalonia turcestanica (Dalla Torre, 1897) is resurrected from synonymy. P. albohirsuta Tsuneki, 1971 is newly recorded for Kazakhstan and P. hirsutaffinis (Tsuneki, 1971) for Kyrgyzstan and Russia.